Preeclampsia and superimposed preeclampsia: The same disease? The role of angiogenic biomarkers. (2nd April 2016) - Costa, Rafaela A.; Hoshida, Mara S.; Alves, Eliane A.; Zugaib, Marcelo; Francisco, Rossana P. V.
ABSTRACT: Objective : We aimed to compare sFlt-1 and placental growth factor (PlGF) levels and the sFlt-1/PlGF ratio between women with preeclampsia and superimposed preeclampsia to, respectively, normotensive and chronic hypertensive ones. Study design : We performed a prospective two-armed cohort in a tertiary teaching hospital in Sao Paulo, Brazil, including 37 normotensive and 60 chronic hypertensive pregnant women. We assessed the serum levels of sFlt-1 and PlGF at 20, 26, 32, and 36 gestational weeks by enzyme-linked immunosorbent assay. Main outcome measures : Having preeclampsia and superimposed preeclampsia. Results : Among normotensive and chronic hypertensive pregnancies, 4 (10.8%) and 14 (23.3%) women developed preeclampsia and superimposed preeclampsia, respectively. Compared with those who remained normotensive, the preeclampsia women presented higher sFlt-1 levels at 32 gestational weeks (4323.45 pg/mL vs. 2242.04 pg/mL, p = 0.019), lower PlGF levels at 20 (183.54 pg/mL vs. 337.38 pg/mL, p = 0.034), 32 (169.69 pg/mL vs. 792.53 pg/mL, p = 0.001), and 36 gestational weeks (252.99 pg/mL vs. 561.81 pg/mL, p = 0.029), and higher sFlt-1/PlGF ratios at 26 (9.02 vs. 1.84, p = 0.004), 32 (23.61 vs. 2.55, p = 0.001), and 36 gestational weeks (49.02 vs. 7.34, p = 0.029). On the other hand, compared with those who remained chronic hypertensive, the superimposed preeclampsia women only presented a higher sFlt-1/PlGF ratio at 32 gestational weeks (9.98 vs. 2.51, p = 0.039). Conclusion : Although angiogenic imbalance is clearly related to preeclampsia, it seems to play a more modest role in superimposed preeclampsia, in which other mechanisms should also be investigated.